(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2018)
The purpose of this research is to study the Variable Similarities of the word place of a word or phrase in the Holy Quran, the collection of the Quranic signs in which the substitution of the word of the word of the word was signed, and the addition of another place from Al-Fath to Al-Waqiaa. The research reached eleven witnesses; The study was based on the extrapolation of the evidence on Ibn al-Zubayr. The Angel of the Crucial Interpretation of Those Who Have Atheism and Interpretation" as one of the most prominent imams of the linguistic guidance of the similarity in the Holy Qur’an. These Qur’anic evidences will be categorized according to similar types of verbal , Of the replacement Word or phrase by another.